The functional antagonist of sphingosine-1-phosphate, FTY720, impairs gut barrier function - Sikdar, Sohini; Mitra, Debmalya; Das, Oishika; Bhaumik, Moumita; Dutta, Shanta (Frontiers in Pharmacology, 2024)
FTY720 or fingolimod is a known functional antagonist of sphingosine-1-phosphate (S1P), and it is effective in treating multiple sclerosis and preventing inflammatory bowel disease (IBD). Evidence shows that its use in mice can increase the susceptibility to mucosal infections. Despite the significant contribution of S1P to barrier function, the effect of the administration of FTY720 on the mucosal barrier has never been investigated. In this study, we looked into how FTY720 therapy affected the function of the gut barrier susceptibility. Administration of FTY720 to C57BL/6 mice enhances the claudin-2 expression and reduces the expression of claudin-4 and occludin, as studied by qPCR, Western blot, and immunofluorescence. FTY720 inhibits the Akt–mTOR pathway to decrease occludin and claudin-4 expression and increase claudin-2 expression. FTY720 treatment induced increased colonic inflammation, with notably greater immune cell infiltration, colon histopathology, and increased production of TNF-α, IFN-γ, CXCL-1, and CXCL-2 than that in control mice. Taking into account the close association of “the leaky gut” and gut dysbiosis among the major diseases, we therefore can infer that the vigilance of gut pathology should be maintained, where FTY720 is used as a treatment option.